Production estimation and delay analyses of a locally fabricated band saw - E Omoniyi, Temidayo; A. Onilude, Musiliu (Journal of Production Engineering, 2020)
The objective of the study was to estimate the productivity of a locally fabricated band saw using delay analyses in order to achieve improved production and judicious utilization of available resources. A time and motion study was applied to collect the data for the processing system, and the data were recorded and processed. The working cycle of the machine was also recorded, along with all variables that affect productivity. The results show that productivity was significantly affected by the log supply characteristics, sawing patterns, maintenance of equipment, and the level of training. This reveals the need to improve equipment availability and maintenance during sawing.